TranZap: An App for Transgender Folks Seeking Gender Affirming Healthcare Providers. (1st August 2022) - Chiang, T; Bachmann, G
ABSTRACT: Introduction: Many transgender individuals seeking healthcare have had at least one negative experience related to being transgender. These experiences included verbal harassment, refusal of treatment, or having to teach Healthcare Providers (HCPs) about transgender people to receive appropriate care. As a result, trans patients may forego seeking healthcare treatment at all or will seek non-traditional healthcare services elsewhere, leading to adverse long-term health outcomes. Objective: We sought to build a transgender health app, TranZap, to empower transgender individuals who are seeking healthcare to be more informed and knowledgeable regarding available gender-affirming HCPs. Methods: A prototype of TranZap, a web-based app, was created using Figma. Functions of the app were determined by crowdsourcing input via Instagram from transgender individuals, and those functions were finalized using feedback from HCPs at RWJMS that work with transgender patients. Bootstrap, Python, and Django were used for front-end, back-end, and database development respectively. Advertisement was launched via Instagram. Results: TranZap is currently undergoing alpha testing and modifications are being made to the app's functions. Advertising has started and TranZap has amassed 224 followers on Instagram. Conclusions: Once alpha testing is complete, beta testing will commence in partnership with a transgender support group. We anticipate ∼200 people to beta test TranZap. When the app is publicly released, metrics of success will be the total number of people who open the app, how many people search for HCPs, and how many cumulative reviews are written. The anticipated launch is the beginning of January 2022. Disclosure: No